A process study of long-term treatment: comparing a successful and a less successful outcome. Issue 4 (2nd October 2018) - Drapeau, M.; Stelmaszczyk, K.; Baucom, D.; Henry, M.; Hébert, C.
Abstract : This study examined therapist technique and patient change in emotional experiencing and defense mechanisms in the successful and unsuccessful long-term psychoanalytic treatments of two male patients. Two consecutive sessions every 6 months were analyzed for each patient. Therapist interventions, patient defense mechanisms, and patient emotional experiencing were assessed using the Psychodynamic Intervention Rating Scale, Defense Mechanism Rating Scale and the Experiencing Scale, respectively. Between and within-session analyses were conducted to determine the impact of the patient's defensive functioning and experiencing on therapist interventions, and the effect of therapist interventions on those same two patient variables. Pearson's Coefficient was utilized for between-session analysis; within-session analysis tracking moment-to-moment changes in patient and therapist functioning was performed using lag sequential analysis. Across therapy, therapist use of Interpretive Interventions was associated with increased emotional engagement and decreased defense maturity; the use of Supportive Interventions had the opposite effect. Within-session analysis revealed that use of Supportive Interventions when emotional engagement is low, followed by interpretative interventions, occurred in the successful case. Persistent use of Supportive Interventions in the context of low emotional engagement was observed in the unsuccessful case. This study suggests that failure to stimulate emotional engagement through interpretation can negatively affect therapeutic outcome.